Silage Crops for Dairy and Beef Cattle I: Corn - Marcelo Wallau; João Vendramini; Adegbola Adesogan; Diwakar Vyas; Kevin Korus (EDIS)
This publication covers crop choices and agronomic aspects of silage production in Florida, from planting until preparing to harvest, for corn. Written by Marcelo Wallau, Joao Vendramini, Adegbola Adesogan, Diwakar Vyas, and Kevin Korus, and published by the UF/IFAS Agronomy Department, revised February 2022.